An assessment of the use of a new method for teaching and the learning surgical management of unilateral cleft lip, in plastic surgery residents - Rossell-Perry, Percy (2013)
Introduction: A common problem during medical training in surgical areas like plastic surgery, is the absence of proper methods to obtain the necessary surgical skills to address the different pathologies related to this field. The medical training is performed in educational hospitals in Lima, however the methods are limited to the observation or assistance and don't let to the doctor obtain adequate competences to repair surgically this pathology once they finish their training. Material and Methods:This is a descriptive study for the development of the used methodology and a co relational study to evaluate the results obtained with the methodology. This is a quasi experimental study. It is used to third year plastic surgery training surgeons from San Marcos University of Lima and has been done in children with complete unilateral cleft lip attended in Regional Hospitals from Ministry of Health between 2010 and 2011. Results:We haven't seen significant differences between the non-cleft side and cleft side in these parameters: lip height, lip width and vermilion height. We have seen significant differences between the non-cleft side and cleft side in relation with the nasal base width. Conclusions: This developed methodology to teach and learn the upper double rotational advancement technique used in this study is efficient to obtain good results in the surgical management of unilateral cleft lip with our technique by third year training residents in plastic surgery.